Investigating the influence of ambiguity tolerance and resilience on student engagement: A literature review - Kianinezhad, Neda (Universitas Muhammadiyah Malang, 2024)
The field of education has experienced a profound impact with the emergence of positive psychology (PP), leading to a heightened emphasis on engagement as a crucial construct. Simultaneously, individual differences, particularly ambiguity tolerance, have gained recognition for their pivotal role in the learning process and their influence on learners' engagement. In contrast, resilience has emerged as a potent tool for engaging English as a foreign language (EFL) learners, empowering them to adeptly navigate and overcome challenging circumstances and setbacks. However, despite the acknowledged significance of ambiguity tolerance and resilience in educational contexts, their roles within the domain of foreign language learning remain underexplored. This review sets out to investigate the influence of ambiguity tolerance and resilience on EFL learners' engagement. The study presents compelling evidence, underscoring the substantial roles that ambiguity tolerance and resilience play in fostering learners' engagement. The major finding of this research is the identification of ambiguity tolerance and resilience as crucial factors in enhancing EFL learners' engagement. Following that, building upon these findings, the paper offers practical implications and suggestions for effectively integrating these constructs into foreign language education. Finally, the ultimate goal is to enhance students' overall engagement and enrich their learning experiences.